1997
DOI: 10.1021/es960748a
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization Kinetics of Stilbene-Type Fluorescent Whitening Agents

Abstract: Photoisomerization of stilbene-type fluorescent whitening agents (FWAs) is an important process that governs their isomer distributions and photodegradation rates in the aquatic environment. Kinetic expressions relating parameters for singlet excited-state dynamics, photoisomerization, and photodegradation were derived. Picosecond timecorrelated single photon counting and stationary monochromatic irradiation were used to study the fluorescence lifetimes and steady-state isomer ratios of three widely used FWAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…These values correspond to measured values in lake and coastal waters (Hayashi et al, 2002;Kramer, Canonica, Hoigné, & Kaschig, 1996). Photodegradation of FWAs is slowed by the presence of dissolved organic matter, and DSBP was degraded three times faster (t1/2 = 87 min) than DAS1 (t1/2 = 278 min) in lake water under summer noon sunlight (Canonica et al, 1997).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…These values correspond to measured values in lake and coastal waters (Hayashi et al, 2002;Kramer, Canonica, Hoigné, & Kaschig, 1996). Photodegradation of FWAs is slowed by the presence of dissolved organic matter, and DSBP was degraded three times faster (t1/2 = 87 min) than DAS1 (t1/2 = 278 min) in lake water under summer noon sunlight (Canonica et al, 1997).…”
Section: Introductionsupporting
confidence: 85%
“…A simulation study for FWAs photoisomerization in fresh water showed that the E,Eisomer fraction of DSBP was 75%-86% and E-isomer fraction of DAS1 was 7%-18% (Canonica, Kramer, Reiss, & Gygax, 1997). These values correspond to measured values in lake and coastal waters (Hayashi et al, 2002;Kramer, Canonica, Hoigné, & Kaschig, 1996).…”
Section: Introductionsupporting
confidence: 70%
“…One of the major photoreactions causing loss of fluorescence is trans(e) -*• cis(z) isomerization, a reaction which involves rotation of the stilbene molecule around the central ethylene bond [14][15][16], The photochemical process of trans-cis isomerization is illustrated in Scheme 2. The mechanism of the emissionless deactivation of the singlet state FBs is in fact a conformation transition of a singlet excited state of the trans isomer being in the eis form accompanied by a well pronounced non-radiative emission -*• S 0 .…”
Section: Resultsmentioning
confidence: 99%
“…The photo-induced hydrolyzation and trans-cis photoisomerization of TFBs on cotton fabrics as shown in Schemes 2 and 3 always exist from the beginning of illumination to the end of moisture volatilization [4,8,[26][27][28][29][30].…”
Section: Effect Of Wet Condition On Photo-fading Of the Tfbsmentioning
confidence: 99%